2023
DOI: 10.1021/acsphotonics.3c00662
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-Compatible In Situ Strain Tuning of 2D Material-Integrated Nanocavity

Abstract: Tunable nanophotonic resonators are an essential building block for material-integrated photonic systems and solidstate cavity quantum electrodynamic experiments. Matching the cavity resonance with the material optical transition is crucial for enhancing the light−matter interaction, leading to various associated phenomena that have important implications in quantum optics and optoelectronics. However, our inability to precisely control the resonant wavelength of nanofabricated optical cavities necessitates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…For instance, recent work on in-situ strain tunable suspended cavities shows the potential that EHDIJ printing could have for integrating a broad range of colloidal emitters into actively tunable photonic devices. [56] Lastly, a significant contribution to the broad line widths of the as-printed QDs is due to the variation among emitters in an aggregate deposition. Seeking out reliable methods for deterministically positioning single QDs is becoming a focus for those interested in functionalizing colloidal emitters for their potential in single-photon manipulation and entanglement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent work on in-situ strain tunable suspended cavities shows the potential that EHDIJ printing could have for integrating a broad range of colloidal emitters into actively tunable photonic devices. [56] Lastly, a significant contribution to the broad line widths of the as-printed QDs is due to the variation among emitters in an aggregate deposition. Seeking out reliable methods for deterministically positioning single QDs is becoming a focus for those interested in functionalizing colloidal emitters for their potential in single-photon manipulation and entanglement.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, recent work on in‐situ strain tunable suspended cavities shows the potential that EHDIJ printing could have for integrating a broad range of colloidal emitters into actively tunable photonic devices. [ 56 ]…”
Section: Resultsmentioning
confidence: 99%
“…Strain may also be actively tuned in situ when the monolayer is deposited on top of a piezo-responsive material. [176,177] Ref. [176] showed that single photon emitters in WSe 2 defined along a wrinkle may be tuned in emission energy over a range as wide as 18 meV.…”
Section: Specific Advantages Of the Materialsmentioning
confidence: 99%